Performance benchmarking of four cell‐free protein expression systems. Issue 2 (7th October 2015) - Gagoski, Dejan; Polinkovsky, Mark E.; Mureev, Sergey; Kunert, Anne; Johnston, Wayne; Gambin, Yann; Alexandrov, Kirill
ABSTRACT: Over the last half century, a range of cell‐free protein expression systems based on pro‐ and eukaryotic organisms have been developed and have found a range of applications, from structural biology to directed protein evolution. While it is generally accepted that significant differences in performance among systems exist, there is a paucity of systematic experimental studies supporting this notion. Here, we took advantage of the species‐independent translation initiation sequence to express and characterize 87 N‐terminally GFP‐tagged human cytosolic proteins of different sizes in E. coli, wheat germ (WGE), HeLa, and Leishmania ‐based (LTE) cell‐free systems. Using a combination of single‐molecule fluorescence spectroscopy, SDS‐PAGE, and Western blot analysis, we assessed the expression yields, the fraction of full‐length translation product, and aggregation propensity for each of these systems. Our results demonstrate that the E. coli system has the highest expression yields. However, we observe that high expression levels are accompanied by production of truncated species—particularly pronounced in the case of proteins larger than 70 kDa. Furthermore, proteins produced in the E. coli system display high aggregation propensity, with only 10% of tested proteins being produced in predominantly monodispersed form. The WGE system was the most productive among eukaryotic systems tested. Finally, HeLa and LTE show comparable protein yields that are considerably lower than the ones achieved in the E. coli and WGE systems. The protein products produced in the HeLa system display slightly higher integrity, whereas the LTE‐produced proteins have the lowest aggregation propensity among the systems analyzed. The high quality of HeLa‐ and LTE‐produced proteins enable their analysis without purification and make them suitable for analysis of multi‐domain eukaryotic proteins. Biotechnol. Bioeng. 2016;113: 292–300. © 2015 Wiley Periodicals, Inc. Abstract : Here the authors benchmarked the quantity and quality of the protein products produced by four cell‐free protein expression systems based on lysates from Escherichia coli, Wheat germ (WGE), HeLa and Leishmania tarentolae . For this they used a library of 87 most popular human open reading frames in order to compensate for any sequence‐specific biases. The results show that the E. coli and WGE systems achieve higher expression levels, whereas the HeLa and LTE systems excel in quality of the produced proteins.